The Engagement Tradition within the Perspective of Maqasid al-Shariah: A Case Study of Karangnangka Village, Raas District, Sumenep Regency - Kamila Kamila; Nasrulloh Nasrulloh; Ahmad Izzuddin; Thaifur Rasyid (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2025)
This study examines the practice of bhekalan anak ghik dhalem kandungan, a tradition of matchmaking during pregnancy that is still practiced by some people in Karangnangka Village, Raas District, Sumenep Regency. The focus of the research is directed at the socio-cultural background, the dynamics of implementation, and its relevance in the perspective of Maqasid al-Syariah Imam al-Ghazali. This study uses a qualitative case study approach with interview, observation, and documentation techniques, which are analyzed descriptively and interpretatively. The results show that the practice is understood as a symbolic agreement between families that is not legally binding and still provides space for autonomy for children. From the perspective of Maqasid al-Syariah, this practice is considered legitimate as long as it is oriented toward welfare and does not contain elements of coercion, especially in protecting offspring and property without neglecting the protection of children's rights.